2022
DOI: 10.1111/acel.13679
|View full text |Cite
|
Sign up to set email alerts
|

p38α‐MAPK‐deficient myeloid cells ameliorate symptoms and pathology of APP‐transgenic Alzheimer's disease mice

Abstract: Alzheimer's disease (AD), the most common cause of dementia in the elderly, is pathologically characterized by extracellular deposition of amyloid‐β peptides (Aβ) and microglia‐dominated inflammatory activation in the brain. p38α‐MAPK is activated in both neurons and microglia. How p38α‐MAPK in microglia contributes to AD pathogenesis remains unclear. In this study, we conditionally knocked out p38α‐MAPK in all myeloid cells or specifically in microglia of APP‐transgenic mice, and examined animals for AD‐assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 60 publications
(68 reference statements)
2
11
0
Order By: Relevance
“…Indeed, the deficiency of Il-17a abolished the inflammatory inhibition induced by the deletion of gut bacteria in both microglia and brain tissue. However, knockout of Il-17a gene reduces microglial branching in APP-transgenic mice, indicating inflammatory activation of microglia, as shown in our recent project (Luo et al 2022). Thus, Il-17a regulates rather than mediates the effects of gut bacteria on the brain.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Indeed, the deficiency of Il-17a abolished the inflammatory inhibition induced by the deletion of gut bacteria in both microglia and brain tissue. However, knockout of Il-17a gene reduces microglial branching in APP-transgenic mice, indicating inflammatory activation of microglia, as shown in our recent project (Luo et al 2022). Thus, Il-17a regulates rather than mediates the effects of gut bacteria on the brain.…”
Section: Discussionsupporting
confidence: 68%
“…Our recent study showed that Il-17a-expressing CD4-positive lymphocytes increase in the gut and spleen of APP-transgenic mice (Luo et al 2022). We hypothesized that circulating T cells mediate the effects of intestinal bacteria on microglial activation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations